Mechanical Behavior of a Deep-Buried Soft Soil Conveyance Tunnel Crossing Soft-Hard Soil Layers Under High-Pressure Water Conditions - Hao Liu; Zonglong Li; Zhipan He; Tiancheng Wang; Mingfu Ni; Jiali Ren; Xiang Zhang; Xiaofeng Wang (Advances in Civil Engineering)
Deep-buried soft soil water conveyance tunnels traversing multiple geological layers are susceptible to structural damage under dynamic internal water pressure. The cross-layer stratum is particularly sensitive to adverse conditions, such as dynamic internal water pressure and high external water loads. Using the pressurized water conveyance tunnel from the Central Yunnan Water Diversion Project as a case study, numerical analysis of tunnel lining segments under dynamic internal water pressure was conducted using the finite element method (FEM). The mechanical behavior and stress distribution of the lining segments under different water conveyance schemes—including empty, semi-filled, and filled cases—were systematically analyzed in terms of lining stress, deformation, longitudinal and circumferential displacements, and bolt stress. The results indicate that the lining segments experience the maximum external water pressure under an empty case, with the transverse and longitudinal stresses of the lining bolt identified as a critical weak position. As water transitions from an empty to a semifilled status, horizontal expansion deformation of the lining decreases, stress distribution becomes more uniform, and stress concentrations are observed in the vault region. Further transitioning to a filled status leads to a gradual balance between internal and external pressures, resulting in convergent structural deformation. Moreover, the largest lining deformations occur in cross-layer stratum where the tunnel passes through soft-hard soil layers. Additionally, the assembly angle of the lining segments significantly influences the structural stress. As a result, both geological conditions and segment assembly angles should be considered during tunnel design to optimize performance.